Pengaruh Tingkat Pendidikan dan Upah Minimum terhadap Penyerapan Tenaga Kerja di Provinsi Kalimantan Selatan Tahun 2014 – 2018 - A Alamsyah; Muhammad Effendi (PPJP Universitas Lambung Mangkurat, 2020)
This Research was conducted to (1) Determine the influence of education level and minimum wages on labor absorption in 13 districts/cities in South Kalimantan Province; (2) Determine the most dominant factor in influencing labor absorption in the Province of South Kalimantan.This Research is included in the type of quantitative descriptive Research. While the location of this study is 13 districts / cities in South Kalimantan Province, and the object of this study is the data of education level and minimum wage in South Kalimantan during 2014 - 2018. The data obtained is then processed using panel data regression analysis with fixed-effect models using the EVIEWS 10 program.The results of this Research indicate that (1) The level of education and minimum wages simultaneously have a significant effect on labor absorption in the Province of South Kalimantan in 2014 - 2018; (2) The results of this study also indicate that the level of education is the most dominant factor affecting labor absorption in South Kalimantan in 2014 – 2018